2008
DOI: 10.1152/jn.90574.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity of the Human Subthalamic Nucleus in the Parkinsonian and Nonparkinsonian State

Abstract: We recorded resting-state neuronal activity from the human subthalamic nucleus (STN) during functional stereotactic surgeries. By inserting up to five parallel microelectrodes for single- or multiunit recordings and applying statistical spike-sorting methods, we were able to isolate a total of 351 single units in 65 patients with Parkinson's disease (PD) and 33 single units in 9 patients suffering from essential tremor (ET). Among these were 93 pairs of simultaneously recorded neurons in PD and 17 in ET, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
127
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 40 publications
29
127
1
4
Order By: Relevance
“…Several lines of evidence suggest that these results are robust. First, the recording microelectrodes were localized within the STN, as attested by the neuronal activity recorded, which was similar to that previously reported in PD patients (Hutchison et al 1998;Rodriguez-Oroz et al 2001;Steigerwald et al 2008). Second, the location of recorded STN single cells and stimulating electrodes were precisely determined using a validated threedimensional histological deformable BG atlas (Yelnik et al 2007;Bardinet et al 2009).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Several lines of evidence suggest that these results are robust. First, the recording microelectrodes were localized within the STN, as attested by the neuronal activity recorded, which was similar to that previously reported in PD patients (Hutchison et al 1998;Rodriguez-Oroz et al 2001;Steigerwald et al 2008). Second, the location of recorded STN single cells and stimulating electrodes were precisely determined using a validated threedimensional histological deformable BG atlas (Yelnik et al 2007;Bardinet et al 2009).…”
Section: Discussionmentioning
confidence: 58%
“…Second, neuronal activity was sampled for each period, and epochs of elevated discharge rate were analyzed for bursts using a Poisson surprise analysis (Legendy and Salcman 1985) carried out using a Spike2 script (Degos et al 2005). In this experiment, spike trains with spikes of more than five were considered to be bursts (Steigerwald et al 2008). The mean burst frequency, duration, number of spikes per burst, intraburst frequency, and interburst interval were calculated for each neuron with burst discharges (Steigerwald et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have linked synchronization in the basal ganglia-thalamocortical circuit that occurs at frequencies within the 3-10 Hz band [44,120,197,207] and beta band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [111,113,175,223] with PD. The beta (13-30 Hz) oscillations are probably driven from the motor areas of the cortex, but at tremor frequencies (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, single-unit and/or local field potential (LFP) recordings have demonstrated that the external part of the globus pallidus (GPe) and the subthalamic nucleus (STN) exhibit a tendency to oscillate and synchronize at low frequencies in the parkinsonian state [20,34,130,155,176]. The pathophysiological betafrequency oscillations (13-30 Hz) are thought to be responsible for bradykinesia and rigidity in PD patients [111,113,175,223], whereas the 3-10 Hz oscillations have been associated with tremor [44,120,197,207].…”
Section: Introductionmentioning
confidence: 99%